Using a novel spiral-filter press technology to biorefine horticultural by-products: The case of tomato. Part I: Process optimization and evaluation of the process impact on the antioxidative capacity. (December 2016) - Kips, Lies; De Paepe, Domien; Bernaert, Nathalie; Van Pamel, Els; De Loose, Marc; Raes, Katleen; Van Droogenbroeck, Bart
Abstract: With tomato as a model crop, the use of a novel, low-oxygen spiral-filter press technology for juice production was demonstrated on pilot-scale. Our results show that a robust process could be developed with a juice yield of 82.5% which could be increased to 97.0% with an additional mild thermal pretreatment (40 °C for 3 min). A comprehensive insight was gained in the underlying mechanisms through which process parameters can affect juice yield and juice quality parameters such as turbidity and precipitate weight ratio. Additionally, the antioxidative capacity (AOC) was investigated, showing a preservation of antioxidants during pressing (102 ± 12%) which may be attributed to the low-oxygen processing. Finally, also an insight was gained in the antioxidative distribution of the resulting fractions, demonstrating the potential of the press residue and confirming the relevance of designing a biorefinery system where all fractions are valorized. Industrial relevance: This pilot-scale study illustrates the potential of a novel spiral-filter press technology in refining biomass. Besides a high juice yield and retention of the antioxidative potential, it proves flexible towards characteristics of the input biomass and can customize end-products in function of the aimed application. This study contributes to the essential technical knowledge necessary for processing other matrices with this novel technology. Highlights: A concept for biorefining perishable food losses is proposed using a novel technology. Using the low-oxygen spiral-filter press on tomato led to a juice yield of 82.5%. This could be increased to 97% with an additional thermal pretreatment. A comprehensive insight is gained in the process impact on the juice production. The antioxidant capacity of the tomato is conserved throughout pressing (102 ± 12%).